Frameworks used for IT governance at universities: An exploratory study - Bianchi, Isaías Scalabrin (2018)
Frameworks are essential to assist the organizations with the implementation of effective IT governance. COBIT and ITIL, among other frameworks, can be considered for the implementation of IT governance. This work uncovers which frameworks and related standards have been adopted to implement the governance of IT at universities. Using a qualitative approach, interviews were carried out with IT directors at universities in three countries: Brazil, Portugal, and the Netherlands. Findings reveal that ITIL is the most used framework with Service Desk and Incident Management as the most implemented processes in the six universities under study. While the Brazilian and the Portuguese universities have adopted ITIL, the Dutch universities preferred to adopt BiSL. Something similar happens for IT project management with Brazilian and Portuguese universities adopting PMBOK while Dutch universities have adopted PRINCE2. Something that is common to all universities under study, it is the option for IS0:27001 regarding information security. Overall, it seems that IT at universities is still focused on operational and managerial issues. The case for the governance of IT is still to be made in order to make clear that IT can play a crucial role to deliver a winning strategy in the business of higher education.